2016
DOI: 10.1016/j.pbiomolbio.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular motions that shape the cardiac action potential: Insights from voltage clamp fluorometry

Abstract: Very recently, voltage-clamp fluorometry (VCF) protocols have been developed to observe the membrane proteins responsible for carrying the ventricular ionic currents that form the action potential (AP), including those carried by the cardiac Na þ channel, Na V 1.5, the L-type Ca 2þ channel, Ca V 1.2, the Na þ /K þ ATPase, and the rapid and slow components of the delayed rectifier, K V 11.1 and K V 7.1. This development is significant, because VCF enables simultaneous observation of ionic current kinetics with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 150 publications
(179 reference statements)
0
16
0
Order By: Relevance
“…Because computational models of channels are readily incorporated into multiscale cell and tissue models, 136,138 this approach could be used to identify how inactivation should be targeted therapeutically to stabilize excitation at the tissue level to prevent arrhythmia. As additional structural data emerges, including the Cryo-EM structure of a mammalian Na V channel, 139 conformational data from fluorescence experiments, 140 and even NMR data showing channel dynamics, 141 these models will only improve, provided that the computational approaches needed to incorporate this type of information into the models continue to be developed in parallel.…”
Section: Toward Molecularly Detailed Models Of Inactivationmentioning
confidence: 99%
“…Because computational models of channels are readily incorporated into multiscale cell and tissue models, 136,138 this approach could be used to identify how inactivation should be targeted therapeutically to stabilize excitation at the tissue level to prevent arrhythmia. As additional structural data emerges, including the Cryo-EM structure of a mammalian Na V channel, 139 conformational data from fluorescence experiments, 140 and even NMR data showing channel dynamics, 141 these models will only improve, provided that the computational approaches needed to incorporate this type of information into the models continue to be developed in parallel.…”
Section: Toward Molecularly Detailed Models Of Inactivationmentioning
confidence: 99%
“…For many years, this protocol has been applied to study the skeletal muscle isoform Na V 1.4, and it has provided great insight into the VSD roles in determining activation and inactivation gating kinetics (Cha et al, 1999; Chanda and Bezanilla, 2002 ; Silva and Goldstein, 2013a , b ), the mechanisms of local anesthetic regulation of the VSDs ( Muroi and Chanda, 2009 ; Arcisio-Miranda et al, 2010 ), and details of how toxins pathologically affect VSD activation ( Campos et al, 2007 , 2008 ). We have recently broadened this approach by developing VCF constructs to track VSD conformations of all four domains in the cardiac paralog, Na V 1.5 ( Varga et al, 2015 ; Zhu et al, 2016 ), whose ionic current modulation by the β subunit in oocytes mirrors the mammalian cell phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently developed VCF protocols for hNa V 1.5 and observed that the DIII-VSD was uniquely immobilized by prolonged inactivation-inducing pulses (Varga et al, 2015; Zhu et al, 2016). Here, we apply these methods to observe the VSD effects of inactivation-deficient mutations within the DIII–DIV linker, the DIII S4–S5 linker, and the DIV S4–S5 linker to discover how they interact to regulate Na V channel inactivation.…”
Section: Introductionmentioning
confidence: 99%